Masking terror : how women contain violence in Southern Sri Lanka - Argenti-Pillen, Alex (Ethnography of political violence., 2003)
"In Sri Lanka, staggering numbers of young men were killed fighting in the armed forces against Tamil separatists. The war became one of attrition - year after year waves of young foot soldiers were sent to almost certain death in a war so bloody that the very names of the most famous battle scenes still fill people with horror. Alex Argent-Pillen describes the social fabric of a rural community that has become a breeding ground and reservoir of soldiers for the Sri Lankan nation-state, arguing that this reservoir has been created on the basis of a culture of poverty and terror.